Implementasi Metode STAD dalam Meningkatkan Hasil Belajar Matematika - Akhamd Alfaeni; Nurhidayah Nurhidayah; Atim Rinawati (IAINU Kebumen, 2022)
This study aims to improve mathematics learning outcomes through the STAD method in classV MI Dipanegara Ranterejo. The subjects of this study were 14 students of MI DipanegaraRanterejo. This type of research is Classroom Action Research. The research was carried out intwo cycles, each cycle carried out three times of learning and test sessions. Data collectiontechniques using observation, interviews, documentation and tests. Technical data analysis usingdata reduction, data presentation, and conclusions. The results show that the STAD method canimprove student learning outcomes. Results Based on the research and discussion obtained,learning outcomes increased from an average value of 68.09 in the first cycle to 84.28 in the secondcycle